Quercetin Potently Reduces Biofilm Formation of the Strain Pseudomonas aeruginosa PAO1 in vitro - Pejin, Boris; Ciric, Ana; Jasmina; Glamoclija, Jasmina; Nikolic, Milos; Stanimirovic, Bojana; Sokovic, Marina (Current Pharmaceutical Biotechnology, 2015)
This work was focused on in vitro evaluation of anti-biofilm and anti-quorum sensing effects of four selected flavonoid compounds /(+)-catechin, caffeic acid, quercetin and morin/ using the strain Pseudomonas aeruginosa PAO1. At a concentration of 0.5 MIC quercetin was the only compound found to potently reduce both P. aeruginosa biofilm formation (95%) and its twitching motility. The chemical scaffold of quercetin, a common dietary polyphenol, may actually inspire development of novel and more effective medicinal agents targeting P. aeruginosa, the bacterium well known for its resistance.
Keywords: Anti-quorum sensing effects